PENGARUH PROFESIONALISME DAN MORALITAS PELAKSANA WERVING TERHADAP KUALITAS TAMTAMA PRAJURIT KARIR TNI ANGKATAN LAUT - Heri Tristiawan; Aria Yoedistira (BBM (Buletin Bisnis & Manajemen), 2022)
This research was conducted to determine the effect of professionalism and morality of werving implementers on the quality of the TNI AL's primary career soldiers. This study uses a quantitative method, where the data collected is analyzed in stages starting from the validity and reliability tests of the instruments of professionalism and morality and the quality of the recruitment results, then followed by a normality test using the Kolomogorov-Smirnov test method. The data were obtained from questionnaires of 54 Lapetal personnel. The results of this study using SPSS-25 concluded that the professionalism of werving executors was 18.4% and the morality of the werving implementers had an effect of 6.7% on the quality of the recruits for enlisted soldiers of the Navy's career soldiers. That is, simultaneously the professionalism and morality of the werving implementers has an effect value of 26.4% on the quality of the enlisted recruitment results of the Navy's career soldiers, the remaining 73.6% is influenced by other factors that are not examined.